MEJA KURSI BELAJAR DAN BERMAIN ANAK USIA 4-5 TAHUN DENGAN PERMAINAN BENTUK GEOMETRIS - Ahmad Zainudin (Universitas Islam Nahdlatul Ulama Jepara, 2010)
Basically, every child has the potential for creative, even though the level creativity different. Creativity, as well as the potential of each other, need to be given the opportunity and environment by excitative to grow. The development of creativity children are not only influenced by the psychological environment, but also the physical environment has a big influence. The influence from the outside as a constructive form, the bright colors stimulate emotional and psychological child coupled with the type of games that stimulate their intellect compound. Learning facilities and infrastructure as one of the physical environment can act as a stimulus to develop the creativity of children, as external stimulus. Research with the observation method to obtain physical data and the subject obtained directly on the institution and play nursery - a child as a foothold to make the design of tables and chairs that match the child's development. Furniture that has a learning function as a place to learn and play is adjusted with the psychological development of children stimulate creativity with the geometrical forms of the game that will maximize the potential of children. With the design criteria table chairs children learn with the appropriate activities and child development, namely: 1. The use of wood and finishing materials in a safe (non toxic) for children's activities. 2. Design and form of tables and chairs which are in accordance with the psychology of children pekembangan playful, berekplorasi, berimaginasi and experiment with it - it's new and meet the needs of children. 3. Construction is strong and safe for children, children's activities, which tend to be free, where the physical and creative development of children more dominant than the logic or the ratio of children. 4. Color - the bright colors which are applied on the study table and chair children's playground have a good psychological effect for the emotional development of children. The process through which the early stages, preparation and selection of mahogany timber in accordance with the needs of the product, done by expert craftsman to get the perfect job and painted the finishing stage as final. Design furniture and learn to play to stimulate creativity children aged 4-5 years with the geometrical forms of the game will influence and provide a real contribution to the nursery children - a child in developing the potential of children have been born since.